Radioprotective Effects of Zinc and Selenium on Mice Spermatogenesis - H., Bagheri (J Biomed Phys Eng, 2020)
BACKGROUND: Spermatogenesis system is one of the most radiosensitive organs in the body. A usual therapeutic dose of radiation such as the conventional 2 Gy in each fraction of radiotherapy and lower doses seen in diagnostic radiology or a radiation disaster affect the process of spermatogenesis potently. Selenium and zinc are two important elements playing key roles in the development of sperms and also have radioprotective effects. OBJECTIVE: In this study aims to evaluate the radioprotective effect of zinc and selenium against radiation-induced mice testis injury. MATERIAL AND METHODS: In this experimental study, 30 mice were divided equally into 6 groups, including control selenium treated, zinc treated, radiation, radiation + selenium, radiation + zinc. Treatments started from 2 days before irradiation with 2 Gy cobalt-60 gamma rays. After 37 days, all mice were killed for histopathological evaluations. RESULTS: Results showed that exposure to radiation caused a potent effect on spermatogenesis system. Treatment with selenium reversed these radiation effects potently, while zinc had some limited protective effects. Zinc treatment itself caused a detrimental effect on epididymis and, in combination with radiation, it leads to more damage to seminiferous tubules. CONCLUSION: In contrast to previous studies that proposed zinc to protect spermatogenesis against various toxic agents, results of this study showed that although zinc may protect from some parameters, it potentiates radiation damage on seminiferous tubules and has a detrimental effect on the epididymis. By contrast, zinc and selenium could alleviate radiation-induced toxicity on the most of the evaluated parameters.